Analysis of the Role of Providing Quality Customer Service and Promotion of Purchasing Decisions - Dedy Syahyuni (ProBisnis : Jurnal Manajemen, 2023)
This paper examines the relationship between the quality of service provided by marketing personnel in the field to consumers, sales promotions for these products, and their relationship with the purchasing decisions made by consumers. This paper uses a quantitative method with the help of SPSS data processing tools version 21 and MS Excel. The data used are visitors who come to PT Sumber Alfaria Trijaya Tbk Palosan branch, Magelang, with 97 respondents. While the significance level used is 5%. The conclusion of the study is that there is an influence of service quality and sales promotion on purchasing decisions.